Avaliação do Programa de Ação Integrada para Aposentado - Pai - Cruz, Telma Efigênia Tenório (2010)
This is an evaluation study carried out in Fortaleza between August 2009 and January 2010. It was aimed to evaluate the Integrated Action Program for the Retired Population (PAI) regarding its limitations and possibilities. Questionnaires were answered by 90 individuals, i.e. 30% of the total population served by the program in 2009. 20 of them underwent a deeper interview as well. Finally, 08 subjects who do not participate in the program anymore were also interviewed. The analysis of both the qualitative and quantitative data was done considering the regulatory framework in effect in Brazil and the theoretical base recently published in the literature. We found that the program suffers from a significant fragility as a public policy, considering that its funding has been cut by the elected officials and coordinators, the number of technicians was reduced, where some of them are outsourced or even volunteers, there is no regular or sufficient budget to fund a significant part of the promoted activities, it does not have its own offices, serves an abysmally small number of potential beneficiaries, and only functions on a regular basis in Fortaleza although a significant number of retirees and pension beneficiaries linked to the PAI live in other counties within the State of Ceara. The profile of the retired and pension beneficiaries linked to the PAI and who responded to the questionnaire revealed a mean age of 67.8 years, dominance of female, single, widowed, separated/divorced individuals, healthy and with the ability to perform various activities. They were the main source of income in their households. These individuals have an educational level much higher than the population mean, and a monthly income much higher than that of the Brazilian worker. They also own their own house. Most of them evaluated the PAI in an extremely positive fashion, reporting an improvement in what they see as their quality of life and their relationship with other people, both within their household and outside. The 20 interviewed people who are still participating in the PAI have projects for the future, although most of them are not too ambitious. When we compared the profile of the subjects participating in the PAI to that of those not participating in the program, we found some discrete differences: The latter were proportionally older, lonelier and had more health or motor problems. A higher number of such subjects was the household provider and had a gross monthly income lower than those participating in the PAI. One of them even criticized the program. We concluded that the PAI is a public policy with a minimal expression, among other things because it was reformulated and almost does not serve low-income individuals residing in the periphery of Fortaleza and other counties throughout the state. Suggestions: The PAI should be transformed into an Institute with its own headquarters and fit to meet the needs of the majority of its potential beneficiaries; residents of peripheral boroughs in Fortaleza should have a better access through comfortable buses linking them directly to the PAI offices; diversify the activities to also serve those in need of professional requalification to increase their monthly income; guarantee a regular and sufficient budget to fund activities in the rest of the state; create a consulting council for the program, with representatives of the beneficiaries and organizations representing the elderly. KEY WORDS: Aging. Retirement. Integration. Socialization. Evaluation. Public Policies